Experimental study on dew point corrosion characteristics of the heating surface in a 65 t/h biomass-fired circulating fluidized bed boiler. (5th March 2016) - Wang, Yungang; Ma, Haidong; Liang, Zhiyuan; Chen, Heng; Zhao, Qinxin; Jin, Xin
Highlights: Dew point corrosion and ash deposit tests in a biomass-fired boiler were performed. The XRD, XRF and SEM methods were used to analyze corrosion samples. The deposits were made up of ash deposit layer, coupling layer and corrosion layer. The metal matrix simultaneously confronted chlorine corrosion and oxygen corrosion. Abstract: The dew point corrosion characteristics of the heating surface in a 65 t/h biomass-fired circulating fluidized bed (CFB) boiler were experimentally studied. The cross-sectional morphology and composition of the ash deposition were analyzed by scanning electron microscope (SEM), X-ray diffraction (XRD) and X-ray fluorescence spectrum (XRF), respectively. The results showed that the test tube surface was covered by ash deposit layer, coupling layer and corrosion layer. The ash deposit layer and the coupling layer were prone to spall off together. The coupling layer consists of partial ash and corrosion products. The corrosion layer was mainly composed of chlorides (FeCl3, FeCl2, and FeOCl) and oxides (FeOOH, Fe2 O3 ). With the increase of the tube wall temperature, the corrosion depth decreased dramatically and the dew point corrosion was alleviated efficiently. The metal matrix simultaneously suffered from chlorine corrosion and oxygen corrosion. As the tube wall temperature was above water dew point, the main corrosion mode was oxygen corrosion. As the tube wall temperature was below water dew point, the main corrosion mode was chlorine corrosion.